Proceedings of the 2015 10th Joint Meeting on Foundations of Software Engineering 2015
DOI: 10.1145/2786805.2786827
|View full text |Cite
|
Sign up to set email alerts
|

Summarizing and measuring development activity

Abstract: Software developers pursue a wide range of activities as part of their work, and making sense of what they did in a given time frame is far from trivial as evidenced by the large number of awareness and coordination tools that have been developed in recent years. To inform tool design for making sense of the information available about a developer's activity, we conducted an empirical study with 156 GitHub users to investigate what information they would expect in a summary of development activity, how they wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 62 publications
0
35
1
1
Order By: Relevance
“…A more complete list of approaches to quantify productivity on the technical factors can be found in our previous work [5]. Most of these measures only capture a small part of a developer's work, also making it difficult to provide a more holistic picture of a developer's work and productivity [49]. The Personal Software Process (PSP) has taken this a step further by focusing on a set of basic metrics, such as time, size, quality, and schedule data, with the aim of improving an individual developer's skills and quality of work [19], [20], [50].…”
Section: Quantification Of Productivity At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A more complete list of approaches to quantify productivity on the technical factors can be found in our previous work [5]. Most of these measures only capture a small part of a developer's work, also making it difficult to provide a more holistic picture of a developer's work and productivity [49]. The Personal Software Process (PSP) has taken this a step further by focusing on a set of basic metrics, such as time, size, quality, and schedule data, with the aim of improving an individual developer's skills and quality of work [19], [20], [50].…”
Section: Quantification Of Productivity At Workmentioning
confidence: 99%
“…Furthermore, we expect that the voluntary use of such applications and its ability to tailor to the individual is important for its success since it focuses on the intrinsic motivation of developers to improve or better understand themselves. Requiring the use of such tools by upper management on the other hand will lead to a 'gaming' as previous research found and suggested (e.g., [49]), since developers might fear that the gathered information could influence their employment and increase pressure.…”
Section: Privacy Concernsmentioning
confidence: 99%
“…Besides software changes, researchers have studied the automatic summarization of other software artifacts, such as source code [26], [30], [45]- [52], bug reports [53]- [56], app reviews [57], developer discussions [58]- [60] and development activity [61]. Concerning source code, some techniques have been proposed to summarize source code based on program analysis and manually-defined templates [45], [47], [49], information retrieval [46], [48], and learning-based methods [26], [30], [50].…”
Section: Summarizing and Documenting Other Software Artifactsmentioning
confidence: 99%
“…Truede et al interviewed GitHub developers about what kind of information should be summarized in a development activity feed. The developers consistently mentioned unusual events as being important . In addition, they propose a dashboard to detect unusual events in commit histories and perform a preliminary evaluation with 6 interviews within a Brazilian company .…”
Section: Related Workmentioning
confidence: 99%
“…The developers consistently mentioned unusual events as being important. 56 In addition, they propose a dashboard to detect unusual events in commit histories and perform a preliminary evaluation with 6 interviews within a Brazilian company. 34 Their interviewees mention similar reasons for what makes commits unusual and their examples of unusual events align with the commits characteristics that we investigate in this paper.…”
Section: Related Workmentioning
confidence: 99%